Implementasi Kompetensi Pedagogik Guru Dalam Perancangan Dan Pelaksanaan Pembelajaran - Firda Khairati Amris; Arief Arafat Hankam (Ikhtisar: Jurnal Pengetahuan Islam, 2023)
The issue that this study will address is knowing the teacher's ability to prepare learning plans. The aim of this research is to find out which pedagogical competencies they possess ultimately influence the learning process. The research methodology used in this study is a literature review. The information used in this study takes the form of sources obtained from relevant articles that will be reviewed, such as Google Scholar. Data collection can be in the form of keywords used to search for articles to be reviewed. The keywords that researchers used when researching articles were "Teacher Pedagogical Competence in Designing and Implementing Learning." The research results were reviewed and analyzed using content scanning, summarized and displayed in a research report. The research results showed that the implementation of teacher pedagogical competence in designing and implementing learning is very important, because it will maximize the teacher's implementation in the classroom so that learning will be easily absorbed by students.